Cone-beam computed tomography-guided volumetric assessment of secondary alveolar bone grafting - Julian A. Erkert; Benito K. Benitez; Yoriko Lill; Sebastian Tapia Coron; Andreas A. Mueller (Scientific Reports)
Abstract This study aimed to develop and implement a standardized 3D workflow for surgical planning and outcome assessment in secondary alveolar bone grafting (SABG) using cone-beam computed tomography (CBCT). A 3D protocol was developed using medically certified software for semiautomatic segmentation, mirroring, voxel-based alignement of the maxilla and volumetric analysis of cleft and graft regions. This workflow was applied on a retrospective cohort of patients with unilateral cleft lip and alveolus (CLA) and/or cleft lip and palate (CLP) who received iliac bone mixed with synthetic biphasic calcium phosphate for bone grafting. CBCT scans (preoperative, immediate postoperative, and six-months follow-up) from 23 patients with unilateral clefts were analysed. The non-cleft side was mirrored to serve as reference for symmetric reconstruction. Measured parameters included alveolar cleft volume, grafted bone volume, integrated bone volume and missing volume. The workflow enabled reliable volumetric quantification. The preoperative cleft volume averaged 1505 mm3 (SD 425 mm3) and graft volume 1983 mm3 (SD 407 mm3). After six months, the mean integrated bone volume was 851 mm3 (SD 294 mm3), corresponding to a mean graft resorption of 57% (SD 13%) and alveolar cleft restoration of 58% (SD 19%). This 3D CBCT-based protocol provides a robust methodological framework for assessing SABG outcomes. It enhances quantification of cleft morphology and graft integration, supporting improved surgical planning, follow-up, and cross-study comparability.